Thermal analysis and experimental design of PVDF-trfe-based pyroelectric sensors for infrared applications - Mohamed Behloul; Essaid Bousbiat; Dalila Yamani; Riyadh Bouddou; Nour Eddine Derguini; Ayodeji Olalekan Salau; Djamel Kendil; Sarra Adiche (Case Studies in Thermal Engineering)
In this paper, the design, analysis, and improvement of a copolymer polyvinylidene fluoride-trifluoro ethylene PVDF-TrFE pyroelectric sensor for infrared detection was investigated. The sensor architecture comprises a multilayer structure consisting of a PVDF-TrFE active layer, a 2 μm air gap for thermal insulation, and a silicon substrate. The finite element method (FEM) and analytical models were then used to analyze the specific parameters determining the sensor's performance. The results show a very high level of correlation between the two methods, with the FEM simulation showing an average error of less than 3 % compared with the analytical techniques. In the optimization process, it was also found that etching a silicon substrate, in particular, improves the device's ability to insulate itself from heat, resulting in a 25 % increase in voltage sensitivity. Further electrical characterization was also carried out using the lock-in technique to determine the sensor's efficiency under different lighting conditions, thus evaluating its functionality as an optoelectrical device. The results confirmed a residual polarization of 9.4 μC/cm2 and a coercive field strength of 80 MV/m for the thermal optimization approach. In addition, the results also revealed that the 30 μm-thick PVDF-TrFE layers produced the highest pyroelectric efficiency, with a yield of 45 μC/m2-K. It was also found that incorporating a 2 μm air gap increased the current response by around 18 %, underlining the role of thermals, highlighting the efficiency of our design, and the contributions of each layer to the sensor performance.